'Re-crisis': Barebacking, sex panic and the logic of epidemic. (October 2015) - Kagan, Dion
Since the 'AIDS Crisis' of the 1980s and early 1990s, the combination of sex between men and epidemic disease has been fertile territory for the production of sex panic. This essay examines a 2007 outburst of Australian news media sex panic surrounding a case of the alleged reckless infection of persons with HIV/AIDS and the controversial practices of anal sex without condoms, or 'barebacking'. The rhetorical inflations surrounding these sexual spectacles may be understood via a model of biopolitical governmentality that Linda Singer (1993 ) called 'the logic of epidemic'. I draw on both Singer's model and work on sex panic to describe this news coverage as an instance of what I call 're-crisis'. 'Re-crisis' involves the revivification of the discourses of an earlier moment of AIDS representation in the service of new cultural and institutional modes of managing HIV/AIDS under neoliberal conditions and in the transformed contexts of HIV/AIDS 'post crisis', which has evolved since the advent of antiretrovirals (c. 1996).